A new prediction model for giant cell arteritis in patients with new onset headache and/or visual loss. (31st December 2022) - Moudrous, Walid; Visser, Leo H.; Yilmaz, Tansel; H. Wieringa, Marjan; Alleman, Tim; Rovers, Jörgen; Houben, Mark P.W.A.; Janssen, Paula M.; J. B. Janssen, Johan; L. Rensma, Pieter; J. F. Brekelmans, Geert
Abstract: Objective: The gold standard for diagnosis of giant cell arteritis (GCA) is a temporal artery biopsy (TAB). We sought for a clinical useful model to predict when an invasive TAB is not necessary to confirm GCA. Methods: A prospective cohort study was conducted with patients > 50 years with possible GCA, presenting with newly onset headache and/or visual loss. Demographical, clinical, laboratory findings and histological data were collected. Results: Fifty-six (70%) of the 94 patients showed 1 or more halos of the superficial temporal artery branches. Ultrasound-guided biopsy was positive in 28 patients (30%). Four independent variables predicted a positive TAB: weight loss, bilateral headache, positive halo sign and thrombocytosis. The ROC of the model had an area under the curve of 0.932 with a PPV of 83% and a NPV of 94%. Conclusions: Weight loss, bilateral headache, a positive halo sign with duplex and thrombocytosis are the most important clinical and laboratory predictors for GCA in a selected group of patients. Significance: In patients > 50 years presenting with new onset headache or visual loss with 3 or more of the above mentioned risk factors, a biopsy of the temporal artery is not needed to confirm the diagnosis GCA. KEY MESSAGES: In our study biopsy of the temporal artery was positive in 30% of the patients with possible GCA Weight loss, bilateral headache, a positive halo sign on duplex and thrombocytosis are predictors for GCA The halo sign had a high sensitivity but a low specificity for a biopsy proven GCA